Speech Performance Project in Teaching Descriptive Writing to Junior High School Students - Samsul Anam (Berkala Ilmiah Pendidikan, 2026)
This study was conducted among seventh-grade students at State Junior High School 01 Simpang, a government-administered lower secondary educational institution located in Ogan Komering Ulu Selatan Regency, South Sumatra Province, Indonesia. Preliminary observations revealed that many students had difficulty composing descriptive paragraphs, particularly in clearly describing objects and in applying correct spelling and punctuation. This problem indicates a gap in students' descriptive writing competence and highlights the need for effective instructional strategies. Therefore, this study aimed to examine the effectiveness of the Speech Performance Project learning model in improving students' descriptive paragraph writing skills. This study employed a quantitative, pre-experimental design with a one-group pretest–posttest. The population consisted of 191 students, and a sample of 32 students was selected as research participants. Data were collected through descriptive paragraph writing tests administered before and after the intervention and analyzed using a paired-sample t-test. The results showed that the mean pretest score was 66.67, which increased to 78.13 after the intervention. The t-test analysis indicated a statistically significant difference between pretest and posttest scores, as the calculated t-value (6.48) exceeded the critical value (2.06) at the 5% significance level. These findings demonstrate that the Speech Performance Project learning model effectively improves students' descriptive paragraph writing skills and provides empirical support for performance-based instructional approaches in language education.